Utilizing microarrays to study posttranscriptional regulatory mechanisms of plants - Gregory, Brian (Henry Stewart Talks, 2009)
mRNA structure, The cap-binding complex is required for proper mRNP assembly, Phenotypes of abh1-1 mutant plants, Altered phyllotaxy in abh1-1 mutant plants, RNA silencing in plants, Arabidopsis whole genome tiling array, High-throughput sequencing of the smRNA-component of the Arabidopsis transcriptome, ABH1 is required for proper mature miRNA levels, 5'-RACE experiments, Loss of ABH1 enhances the developmental defects of a hypomorphic AGO1 allele, RNA degradation, Exosome function in Arabidopsis, Tiling arrays suggest the exosome regulates specific fragments of primary miRNA transcripts, Many of the new transcription units only seen upon exosome-depletion are associated with smRNAs and repetitive elements, A genome-wide atlas of exosome substrates in Arabidopsis
Archived at 2021/02/25